Analisis Strategi Pengembangan Peternakan Sapi Perah Anggota KSU Tandangsari di Kecamatan Tanjungsari - Febiani, Mutia; Herlina, Linda; Firman, Achmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The livestock sector is one part of agribusiness that contributes to food supply, in this case animal protein. Production, breeding, processing, and marketing activities are central to the livestock business, including dairy farming. This study aims to identify and analyze internal (strengths and weaknesses) and external (opportunities and challenges) factors affecting livestock farming, as well as recommend alternative strategies and strategy priorities in order to develop dairy farming. Internal and external factors were evaluated using IFE matrix and EFE matrix, then alternative strategies were determined using IE matrix and SWOT analysis. For strategy prioritization. The research location was selected by purposive sampling by looking at data from internal and external aspects of farms located in the Tanjungsari area with the subject of dairy farmers who are members of KSU Tandangsari. The results of the study showed that the total IFE score of 2.95 and EFE of 2.60 showed that this cooperative was in a fairly good position in managing internal strengths and taking advantage of external opportunities. The IE matrix in the study is in cell 5, in this condition a hold and maintain strategy is needed.